Development of a Brief Client Satisfaction and Quality Improvement Tool for Hospital-Based Violence Intervention Programs: Opportunities for Enhancing Client Perspectives - Rachel K. Myers PhD, MS; Hillary M. Kapa MPH; Stephanie M. Garcia MPH; Laura Vega DSW, LCSW; Joel A. Fein MD, MPH (Journal of Patient Experience)
Hospital-based violence intervention programs (HVIPs) are evidence-informed strategies to promote recovery among victims of violence. Limited tools exist to capture client-reported perspectives of program relevance, responsiveness, acceptability, and impact. We conducted a quality improvement project to develop an HVIP-specific tool that can be used to collect information regarding client satisfaction with services to inform ongoing and future program improvement efforts. Four former adolescent clients and 5 caregivers who received services participated in cognitive interviews to share interpretation of questionnaire items, improvements to response options, comfort responding, and missing topics. Participants demonstrated understanding of survey items and offered alternate wording to improve clarity, reduce redundancy, and clarify response options. Revisions based on participant and staff feedback resulted in a 12-item HVIP Client Satisfaction Questionnaire. Our tool provides an opportunity to collect client-reported perspectives regarding satisfaction and perceived short-term program impact to inform continued improvement activities. This tool could be utilized by HVIPs and other violence prevention programs to engage clients in quality improvement efforts in support of program values to be trauma-informed and client centered.